Membangun Portofolio Digital Guru Sekolah Dasar Melalui Pemanfaatan Google Sites di SDN 8 Cakranegara - Muhammad Erfan; Nurul Kemala Dewi; Siti Istiningsih (Educational Consultant & Counseling Career (EC3) Mataram, 2026)
This community service activity trained elementary school teachers at SDN 8 Cakranegara in building digital portfolios using Google Sites. Despite Google Sites being a free, cloud-based platform accessible through standard Google accounts, its adoption as a professional portfolio medium among elementary school educators remains limited. The training was conducted in 2024, involving the school principal, classroom teachers, and administrative staff, and was structured across eight sequential stages: preparation, introduction to digital portfolio concepts, introduction to Google Sites, portfolio creation practice, mentoring and revision, result presentation, training evaluation, and follow-up. Evaluation results indicated that all implementation indicators were rated within the good category. All participants successfully produced Google Sites-based digital portfolios comprising professional profiles, teaching documents, works and achievements, and teaching reflections. The activity was deemed successful, as participants not only gained conceptual understanding of digital portfolios but also produced active, functional portfolios ready to support career development and professional performance assessment.